Perbedaan Kualitas Hidup pada Wanita Lanjut Usia yang Mengikuti Senam Gerak Latih Otak dan Terapi Musik Angklung - Suci Tuty Putri (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2017)
The increasing of life expectancy should be balanced with the improvement of health service to preserve the quality of life among elderly. That is including various therapy activity program which is believed can increase the quality of life for instance with brain movement exercise and Angklung music therapy. Brain movement exercise is the activity to increase cognitive function, while Angklung music therapy is to developing local wisdom. The aim of this study was to analyze the differences of quality of life among women elderly whose undergo brain movement exercise and angklung music therapy. The study design was an experimental pre and post design without con- trol. The study was taken place at Tresna Werdha Nursing Home. The subject was 30 healthy elderly women, consist of 15 elderly who undergo brain movement exercise and 15 elderly angklung music therapy, whose age were 60-90 years.  The instrument used was WHOQOL-BREF. Shapiro-Wilk test, Kolmogorov-Smirnov, Wilcoxon test, and Mann-Whitney U test were used to analyze the data. The results showed there were difference in the quality of life eldery woman who follow brain movement exercise and angklung music therapy in physical domain (0.009) and enviroment domain (0.000), and there was no significant difference in sosial relationship (0.092) and psychological (0.915). The result showed brain movement exercise and Angklung music therapy could affect the quality of life in certain domains, this was possible because there was various benefit in each therapy program. Therefore it was suggested that brain movement exercise and angklung music therapy were imple- mented in all nursing house units in Indonesia.